2015
DOI: 10.1186/s13643-015-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of antenatal education in small classes on obstetric and psycho-social outcomes - a systematic review

Abstract: BackgroundThe aims of antenatal education are broad and encompass outcomes related to pregnancy, birth, and parenthood. Both form and content of antenatal education have changed over time without evidence of effects on relevant outcomes. The effect of antenatal education in groups, with participation of a small number of participants, may differ from the effect of other forms of antenatal education due to, for example, group dynamic. The objective of this systematic review is to assess the effects of antenatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 36 publications
2
28
0
2
Order By: Relevance
“…These results are consistent with authors that refers to the gap between the expectations of pregnant woman against the pain and the lived experience of labor pain [20]. The scientific evidence, for reasons of quality of studies does not allow even realize a cause-effect relationship between the frequency of prenatal classes and the best/worst preparation for the woman to face the pain [21]. Prenatal classes in Portugal are not pure and there is no regular model, once a mix of currents are applied.…”
Section: Discussionsupporting
confidence: 81%
“…These results are consistent with authors that refers to the gap between the expectations of pregnant woman against the pain and the lived experience of labor pain [20]. The scientific evidence, for reasons of quality of studies does not allow even realize a cause-effect relationship between the frequency of prenatal classes and the best/worst preparation for the woman to face the pain [21]. Prenatal classes in Portugal are not pure and there is no regular model, once a mix of currents are applied.…”
Section: Discussionsupporting
confidence: 81%
“…The classes also promote breast feeding and seek to bolster the participants' confidence in their own ability to manoeuvre through childbirth and transition to parenthood. Communicating information to promote health and reduce risk is another key goal of antenatal education (Brixval et al, 2015). The structure of antenatal classes also enables participants to develop social networks and helps them connect with others in the same situation (Fabian et al, 2005).…”
Section: Editorialmentioning
confidence: 99%
“…Antenatal education may have a role in improving women's and partners' knowledge and confidence in coping at home but a recent systematic review reported a lack of good evidence as to its effectiveness in promoting good obstetric and psychosocial outcomes more generally. 39 The maternity services should consider whether women's information needs are being met. In summary, most women were not particularly worried about early labour and most of those who contacted a midwife at this time felt that they received appropriate advice.…”
Section: Discussionmentioning
confidence: 99%